2004
DOI: 10.1097/01.pcc.0000112521.93714.b8
|View full text |Cite
|
Sign up to set email alerts
|

Terlipressin as rescue therapy for intractable hypotension during neonatal septic shock*

Abstract: There is circumstantial evidence that the administration of terlipressin caused the increase in blood pressure. We suggest that terlipressin should be considered as rescue therapy when high-dose catecholamine therapy does not result in sufficient perfusion pressure. Further investigation is needed to prove terlipressin's effectiveness and safety in infants and children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 10 publications
2
39
0
2
Order By: Relevance
“…18 Assuming no vast changes in atrial pressure, and approximating mean PAP by known formulas, 19 this fact alone accounts for a reduction of pulmonary vascular resistance of about 40%. According to Matok et al, 6 we also found a significant improvement in cardiac performance after TP administration, although intermittent bolus administration of TP is believed to be potentially associated with decreased cardiac output. In particular, we found significant decrease of both left and right ventricles myocardial performance index, a Doppler-derived nongeometric and non-volumetric index, highly advantageous in assessing global cardiac function, expressly in presence of distorted right ventricle shape because of severe PH.…”
Section: Casesupporting
confidence: 56%
See 1 more Smart Citation
“…18 Assuming no vast changes in atrial pressure, and approximating mean PAP by known formulas, 19 this fact alone accounts for a reduction of pulmonary vascular resistance of about 40%. According to Matok et al, 6 we also found a significant improvement in cardiac performance after TP administration, although intermittent bolus administration of TP is believed to be potentially associated with decreased cardiac output. In particular, we found significant decrease of both left and right ventricles myocardial performance index, a Doppler-derived nongeometric and non-volumetric index, highly advantageous in assessing global cardiac function, expressly in presence of distorted right ventricle shape because of severe PH.…”
Section: Casesupporting
confidence: 56%
“…Terlipressin (TP) is a synthetic analog of arginine vasopressin (AVP) successfully used to treat hypotension from several causes. 1,2 In newborn infants, experience with TP use is scarce and mainly limited to the treatment of refractory hypotension of septic origin; [3][4][5][6] however, TP has also been used as a rescue therapy for refractory pulmonary hypertension (PH) associated with congenital diaphragmatic hernia 3,7,8 and therapeutic hypothermia, 3 suggesting a possible vasodilatory effect of TP on pulmonary circulation. We describe our experience with TP in an asphyxiated septic newborn with moderate PH at birth treated with mild whole-body hypothermia, who developed catecholamine-resistant hypotension and exacerbation of PH during passive rewarming.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the use of vasopressin or terlipressin has focused on rescuing newborns with hypotension refractory to standard catecholamines [6][7][8][9][10][11]. A small number of case reports of infant resuscitation with vasopressin or terlipressin have shown prompt reversal of hypotension and improved tissue perfusion, without adverse affects [7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Despite widespread use of vasopressin and its synthetic analogue terlipressin for hypotensive shock in adults [4,5], vasopressin use remains limited in the neonatal population. Case reports and observational studies in neonates, using vasopressin or terlipressin, have suggested a beneficial effect; however, effective dosing, systemic hemodynamics, and local effects upon target organs remain unexplored [6][7][8][9][10][11]. Our objective was to assess the dose-response effects of vasopressin on systemic hemodynamics, along with mesenteric and cerebral perfusion in asphyxiated newborn piglets.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in vasodilatory shock, a relative AVP deficiency exists that may be corrected by administration of AVP. Currently, AVP and its analogue, terlipressin, are being increasingly used as a rescue therapy for hypotension, refractory to high-dose catecholamine and corticosteroids in neonates with sepsis (Matok 2004;Leone 2008;Bidegain 2010), cardiogenic shock (Meyer 2006b;Lechner 2007), necrotizing enterocolitis (Bidegain 2010), non-septic shock with acute renal injury (Meyer 2006a), and systemic inflammatory response syndrome following surgery (Filippi 2008). In neonatal studies, dosages of AVP ranged between 0.01 to 0.36 units/kg/h, and terlipressin from 7 µg/kg twice a day to 2 µg/kg every four hours.…”
Section: How the Intervention Might Workmentioning
confidence: 98%